Golden aid an emergency ambulance system - George, Anita Acha; Krishna, Arun; Dias, Toney; Vargheese, Asheena Sara; Divya, R S (2017 International Conference on Networks & Advances in Computational Technologies (NetACT), 2017)
According to Times of India about 146,133 people were killed in road accidents in India in the year 2016. Unfortunately about 30% of deaths are caused due to delayed ambulance. In today's scenario the number of accidents per day is increasing exponentially and so is the number of deaths caused by it. Golden Aid increases the possibility of saving a life by avoiding the unnecessary time delay of traffic jams during an emergency case. The shortest route to the accident spot is displayed and the central server tracks the vehicles location and switches the traffic signal when the ambulance is nearing the traffic lights. The design and implementation of this technique is directly targeted for traffic management so that emergency vehicle on road gets a clearer way to reach their destination in less time and without any human interfearence.